2010
DOI: 10.1163/001121609x12591347509248
|View full text |Cite
|
Sign up to set email alerts
|

The effects of manipulating water temperature, photoperiod, and eyestalk ablation on gonad maturation of the swimming crab, Portunus trituberculatus

Abstract: An experiment to induce maturation and spawning of Portunus trituberculatus by manipulating seawater temperature, photoperiod, and eyestalk ablation, and to study the effect these factors have on the variation of nucleic acid content in gonadal tissue, was conducted. Non-incubating adult females were divided among three temperature treatments (natural, 10 • C, and 20 • C) and two photoperiod treatments (15 h and 9 h daylight periods per day, respectively). Within each temperature-photoperiod combination, subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The swimming crab, Portunus trituberculatus , is an important marine-culture crab widely distributed in the coastal water area of East Asia, including Korea, Japan, Philippines and China [23, 24]. Previous studies in our group have shown that estradiol widely distributed in various endocrine organs of P .…”
Section: Introductionmentioning
confidence: 99%
“…The swimming crab, Portunus trituberculatus , is an important marine-culture crab widely distributed in the coastal water area of East Asia, including Korea, Japan, Philippines and China [23, 24]. Previous studies in our group have shown that estradiol widely distributed in various endocrine organs of P .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, with the wild seahorse resources had been slumped and the drastic increase in market demand for seahorse, the seahorse breeding industry is growth and booming. However, there are still many problems restricting the production efficiency in the current breeding industry, most of which are caused by environmental stresses within the aquaculture system (Jang et al, 2010; Li & Xiang, 1999; Nicieza & Metcalfe, 1997; Wang et al, 2008). Due to high density in the artificial system, the cultured organisms were in different water layers and positions, in which the environmental factors (such as light, temperature, salinity) were different.…”
Section: Introductionmentioning
confidence: 99%